2020
DOI: 10.1302/2058-5241.5.190068
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary compression screw fixation of metacarpal and phalangeal fractures

Abstract: The intramedullary headless compression screw (IMCS) technique represents a reliable alternative to percutaneous Kirschner-wire and plate fixation with minimal complications. Transverse fractures of the metacarpal shaft represent a good indication for this technique. Non-comminuted subcapital and short oblique fractures can also be treated with IMCS. This technique should not be used in the presence of an open epiphysis, infection and, most of all, in subchondral fractures, because of the lack of purchase for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The long oblique fractures (>2 times the shaft diameter) and comminuted fractures are at risk of fracture displacement and shortening [12]. This percutaneous retrograde intramedullary fixation for metacarpal and phalangeal fractures has gained popularity in the last decade, and the results are promising [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The long oblique fractures (>2 times the shaft diameter) and comminuted fractures are at risk of fracture displacement and shortening [12]. This percutaneous retrograde intramedullary fixation for metacarpal and phalangeal fractures has gained popularity in the last decade, and the results are promising [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The regular complication caused by utilization of K-wire or mini plate was stiffness, flexion contracture and extensor lag [9] . Meanwhile, recent large studies found that intramedullary fixation with headless compression screw is a reliable technique for the treatment of unstable extra-articular metacarpal or proximal and medial phalanx [9] , [10] , [11] . The small incision was made to visualize the extensor tendon in the distal phalanges.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns that are nondisplaced or stable following closed reduction with minimal angulation, shortening, or malrotation can be managed with a short period of immobilization in the intrinsic plus position followed by a range of motion (ROM). 4,10 Surgical indications include open fractures, those with rotational deformity disrupting the digit cascade, unstable patterns, significantly displaced, shortened, or angulated fractures, and patients with multiple phalangeal or metacarpal fractures. 11 The technique of intramedullary screw fixation is best utilized for transverse or short oblique extra-articular fractures of the proximal or middle phalangeal neck or shaft in the index, long, ring, or small digits.…”
Section: Indications/contraindicationsmentioning
confidence: 99%
“…Surgical indications include open fractures, those with rotational deformity disrupting the digit cascade, unstable patterns, significantly displaced, shortened, or angulated fractures, and patients with multiple phalangeal or metacarpal fractures 11. The technique of intramedullary screw fixation is best utilized for transverse or short oblique extra-articular fractures of the proximal or middle phalangeal neck or shaft in the index, long, ring, or small digits 6,10. Certain fractures with partial articular involvement or some degree of metaphyseal or diaphyseal comminution may also be amenable to intramedullary headless screw fixation 12.…”
Section: Indications/contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation